Elevating MSME competitiveness in Labuaja, Maros: A triple-helix approach via business legality, packaging inovative, and digital commercialization - Rasdi Rasdi; Badaruddin Badaruddin; Dirwan Dirwan; Asniwati Asniwati; Un Dini Imran; Hari Hari; Ragdha Meilani Anindia (Community Empowerment, 2026)
This community service program aims to strengthen the competitiveness of small and medium enterprises (SMEs) in Labuaja Village, Maros Regency, particularly traditional palm wine (tuak) and forest honey producers, which have high economic potential but face fundamental constraints. The main challenges include incomplete business legality, unattractive and non-standard product packaging, and limited market access due to the low adoption of digital marketing. This program implements a participatory and integrated assistance model that simultaneously addresses business legality, packaging innovation, and digital marketing initiation within a one-day intensive mentoring framework. Activities were carried out through socialization, direct assistance, and hands-on practices, including creating OSS accounts for Business Identification Number (NIB) registration, label and packaging design using Canva, and creating social media business accounts. The program's effectiveness was evaluated using pre-test and post-test instruments as well as field observations. The results showed an average increase in participants' understanding of 36%, with 40% of SMEs starting NIB registration, 100% successfully producing better packaging designs, and 33% creating digital business accounts. These findings indicate that short-term, practice-oriented, and integrated assistance can effectively improve SMEs' readiness for legal compliance, product value enhancement, and digital market engagement.